2021
DOI: 10.1038/s41598-021-92400-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 viral load in nasopharyngeal swabs is not an independent predictor of unfavorable outcome

Abstract: The aim was to assess the ability of nasopharyngeal SARS-CoV-2 viral load at first patient’s hospital evaluation to predict unfavorable outcomes. We conducted a prospective cohort study including 321 adult patients with confirmed COVID-19 through RT-PCR in nasopharyngeal swabs. Quantitative Synthetic SARS-CoV-2 RNA cycle threshold values were used to calculate the viral load in log10 copies/mL. Disease severity at the end of follow up was categorized into mild, moderate, and severe. Primary endpoint was a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
0
20
0
2
Order By: Relevance
“…Viral burden in SARS-CoV-2 infection is most often quantified by measurement of viral RNA or proteins in the upper respiratory tract. Higher viral load in the upper respiratory tract portends worse outcomes in some studies [7][8][9][10], while others have demonstrated no independent association [11]. Viral load in the upper airways is often not strongly associated with viral products in the plasma [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Viral burden in SARS-CoV-2 infection is most often quantified by measurement of viral RNA or proteins in the upper respiratory tract. Higher viral load in the upper respiratory tract portends worse outcomes in some studies [7][8][9][10], while others have demonstrated no independent association [11]. Viral load in the upper airways is often not strongly associated with viral products in the plasma [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 Given the need for prognostic biomarkers in COVID‐19, several studies have investigated the value of PCR C t , a surrogate measure of viral load, as an outcome predictor in COVID‐19 in the general population. However, varying data ranging from no prognostic value to being a risk factor for mortality have been reported for PCR C t in adults with COVID‐19; 29 , 30 , 31 C t value criteria for demarcation between low and high viral loads remain to be defined. 29 To our knowledge, our study represents the first report of an association between low C t and hospitalization in COVID‐19 in pediatric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, varying data ranging from no prognostic value to being a risk factor for mortality have been reported for PCR C t in adults with COVID‐19; 29 , 30 , 31 C t value criteria for demarcation between low and high viral loads remain to be defined. 29 To our knowledge, our study represents the first report of an association between low C t and hospitalization in COVID‐19 in pediatric cancer. Our results raise the need for further prospective studies investigating C t as a potential biomarker for predicting outcomes in COVID‐19 in pediatric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Viral load may correlate with infectivity, disease phenotype and morbidity in COVID-19 patients, although a higher initial SARS-CoV-2 viral load was associated with increased risk of hospital admission, intensive care unit (ICU) admission and in-hospital mortality in some 9 but not in other studies. 10 Nonetheless, SARS-CoV-2 viral load at diagnosis was an independent predictor of mortality in a large, hospitalised cohort study (hazard ratio 1.07, with a 7% increase in hazard for each log transformed copy per millilitre). 11 A hallmark of effective antiviral therapy is its ability to reduce the viral burden, as evidenced by anti-viral drug therapy for HIV, HCV and herpesviruses.…”
mentioning
confidence: 90%
“…Although PCR can also detect non‐infectious, immune‐complexed viral particles, the correlation of viral load in NPS with infectious SARS‐CoV‐2 has been established in large studies 7,8 . Viral load may correlate with infectivity, disease phenotype and morbidity in COVID‐19 patients, although a higher initial SARS‐CoV‐2 viral load was associated with increased risk of hospital admission, intensive care unit (ICU) admission and in‐hospital mortality in some 9 but not in other studies 10 . Nonetheless, SARS‐CoV‐2 viral load at diagnosis was an independent predictor of mortality in a large, hospitalised cohort study (hazard ratio 1.07, with a 7% increase in hazard for each log transformed copy per millilitre) 11 …”
Section: Introductionmentioning
confidence: 99%